1996
DOI: 10.1097/00000658-199607000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Straight and Colonic J Pouch Anastomosis After Low Anterior Resection

Abstract: Reconstruction with a colonic J pouch was associated with a lower incidence of anastomotic leakage and better clinical bowel function when compared with the traditional straight anastomosis. Functional superiority was especially evident during the first 2 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
265
6
23

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 442 publications
(313 citation statements)
references
References 20 publications
19
265
6
23
Order By: Relevance
“…MRP gradually recovered over time after ISR,14, 15, 19 and anal function improved over time 23, 27. Some authors reported that colonic J‐pouch anastomosis offered superiority in bowel frequency, urgency control, tolerable volume, Wexner score, and fecal incontinence severity index (FISI)77 compared with the straight anastomosis 20, 43, 78. Moreover, the C‐pouch and smooth muscle plasty procedures improved anal function following ISR 30, 44.…”
Section: Discussionmentioning
confidence: 99%
“…MRP gradually recovered over time after ISR,14, 15, 19 and anal function improved over time 23, 27. Some authors reported that colonic J‐pouch anastomosis offered superiority in bowel frequency, urgency control, tolerable volume, Wexner score, and fecal incontinence severity index (FISI)77 compared with the straight anastomosis 20, 43, 78. Moreover, the C‐pouch and smooth muscle plasty procedures improved anal function following ISR 30, 44.…”
Section: Discussionmentioning
confidence: 99%
“…[37] wykazali, że zespolenie koniec-do--końca wiąże się z większym odsetkiem NZ w porównaniu z zespoleniem ze zbiornikiem jelitowym typu "J-pouch" (15% vs 2%; p = 0,03). W innych randomizowanych badaniach wykazano podobny odsetek nieszczelności po zespoleniach bok-do-końca w porównaniu z zespoleniem J-pouch (10% vs 8%) [38], ale wyraźną przewagę rekonstrukcji ze zbiornikiem J-pouch w porównaniu z koloplastyką [39].…”
Section: Jak Zapewnić Optymalne Warunki Do Wygojenia Zespolenia? Sposunclassified
“…Building on successful experience with the ileoanal pouch in familial adenomatous polyposis and ulcerative colitis following proctocolectomy, the colonic J pouch was introduced by Lazorthes and Parc (26,125) The clinical results and manometric data have been compared with straight colorectal and coloanal anastomosis in controlled studies, including numerous randomized trials (29,33,41,54,56,63,88,100,122,123,143,146). According to a meta-analysis (49), the CJP has unique advantages compared with straight coloanal anastomosis: Bowel movement was significantly less up to 2 years after surgery, significantly fewer patients suffered from an imperative urge to defecate up to one year post-operatively and significantly fewer patients had to take antidiarrheals.…”
Section: Colon J Pouch (Cjp)mentioning
confidence: 99%